Spectral and kinetic characteristics of luminescence in CsI-Ca crystals - Myagkota, S.V.; Pushak, A.S.; Stryganyuk, G.B.; Novosad, S.S.; Pashuk, I.P. (Functional Materials, 2008)
The spectral and kinetic luminescence properties of Csl-Ca crystal (Cca = 1 mol. % in the initial melt) have been studied at 10 K and 295 K in the energy range 4-16 eV. The luminescence efficiency has been examined upon the excitation of Csl-Ca within the range of transparency and fundamental absorption of Csl host. The nature of Csl-Ca luminescence is discussed.